Community Empowerment: Used Cooking Oil Recycle to Produce Handwash Soap as a Commercial Souvenir Product in Surakarta - Muhammad Abdus Salam Jawwad; Restu Hikmah Ayu Murti; Praditya Sigit Ardisty Sitogasa (Abdi-mesin: Jurnal Pengabdian Masyarakat Teknik Mesin, 2021)
A community service program was held in Surakarta city, in a boarding school named Kanzus Sholawat to solve the cooking oil waste problem. The used oil which locally is alluded to jelantah oil, blackish brown colored, contains exceptionally high levels of cholesterol, carcinogen, and it may cause harm for human wellbeing. Jelantah oil ordinarily will be directly thrown to the environment, hence may cause water and soil contamination. Agreeing to this, it is essential to teach individuals to do minimization and reuse to the utilized oil (jelantah). Besides, the individuals will be prepared to commercialize the items as a souvenir gift item. The jelantah oil will be processed into handwash cleanser products with a feasible, simple, and cheap procedure and utilizing effortlessly obtained material. To start, a 500 ml of used cooking oil is filtered and mixed with 160 grams of NaOH flakes soluted in 200 ml of water. Some drops of fragrance is added to make the soap perfumed. The purpose of this community service is to provide assistance to the Kanzus Sholawat Surakarta Foundation to take the economic value from the oil waste by commercializing the recycle product. The program will be carried out by training and education to handle the jelantah oil into handwash cleanser, and persistent assessment to make sure the Kanzus Sholawat Surakarta students and adjacent community get the optimal benefits. Pre-order sale system using e-commerce is also expected to be implemented by the students, to make this program sustainable.